Use of Arttherapy Techniques in Pedagogical Accompaniment of Children with Special Educational Needs - Petro Kuzenko; Olexandra Kuzenko; Liudmyla Matsuk (Vasyl Stefanyk Precarpathian National University, 2021)
The article emphasizes the fact that the problem of providing effective pedagogical support for personal development of children with mental and physical disabilities occupies an important place in the educationa theory and practice of modern Ukraine. Among scientists there are different approaches to determining its content, purpose and objectives. Most researchers consider pedagogical support of children with special educational needs (SEN) assystematic actions and measuresaime datensuring positive results in the educational process. The main tasks of pedagogical support of children with psychophysical developmental disorders are to ensure their social adaptation and over come difficulties in communicating with peers; prevention of problems of personal development and upbringing of the child; providing assistance in solving current educational problems and socialization; implementation of psychological and pedagogical counseling for parents. The authorsempha size that art therapy is rightly considered to be an effective means of pedagogical influenceon children with SEN in an inclusive educational space. Art therapy as a method of diagnosis, change and resource development of an individual, group or team through the use of different art sand their own creative activities has a wide field of  application in various areas of  teaching. To achieve a positive result in the pedagogical support of children with SEN the following arttherapy means are used: drawing therapy, fairy-tale therapy, sand therapy, music therapy, photo therapy, color therapy, which can be integrated, completing each other. It is scientifically proven that theuse of different types of arts contributes to the development of a child's emotional and communicative sphere, the establishment of interpersonal communication, taking into account emotional state of peers. During art therapy classes peculiarities of interpersonal communication are revealed, obstacles in its establishment are found and over come, and as a result the development of social-communicatives kills of children with SEN.